Polysulfone and organo-modified graphene oxide for new hybrid proton exchange membranes: A green alternative for high-efficiency PEMFCs. (1st June 2021) - Simari, Cataldo; Lufrano, Ernestino; Brunetti, Adele; Barbieri, Giuseppe; Nicotera, Isabella
Abstract: Novel nanocomposite proton exchange membranes based on an organo-sulfonated derivative of the graphene oxide (SGO) incorporated in sulfonated Polysulfone (sPSU) were successfully fabricated via scalable, cost-effective and eco-friendly solution casting method for high-performing PEM fuel cells. The microstructure, physicochemical features and the electrochemical performance were widely investigated by a combination of various techniques including PFG-NMR spectroscopy, DMA and H2 –O2 single-cell tests. Homogeneous and completely exfoliated sPSU-SGO nanocomposite membranes displayed outstanding thermal and mechanical stabilities as a result of strong interfacial interactions between the graphene nanoplatelets and the sulfonic acid groups on the polymer chains. This, together with the large number of acidic functionalities present in the SGO nanoadditive, greatly improved the water retention capacity of the membrane and increased proton transport through an effective Grotthuss-type mechanism, especially under very low humidification conditions. For instance, at 80 °C and 20% RH, the proton conductivity of the sPSU-SGO membrane was 9.4 mS cm −1 and H2 /O2 cell test yielded a maximum power density of 182.6 mW cm −2 @ 110 °C and 25%RH. These values exceeded that of Nafion 212, used here as a benchmark, demonstrating that this hybrid electrolyte is an interesting and viable candidate for the next generation of high-temperature PEMFCs. Graphical abstract: Graphical abstract Image, graphical abstract